Learners Manipuri-English Dictionary - (:unkn) unknown (Sangam Book Store, Paona Bazar, Imphal- 795001., 2006)
This is a Manipuri-English bilingual dictionary which is particularly helpful for the Manipuri speakers willing to learn English.
Keywords: Manipuri; Learners Manipuri-English Dictionary; Dictionary; Manipuri; English